Causes of regional variation in healthcare utilization in Germany - Martin Salm; Ansgar Wübker (RWI - Leibniz-Institut für Wirtschaftsforschung, 2017)
Healthcare utilization varies widely between regions. Yet, the causes of regional variation are still not well understood, and they can also differ between countries and institutional settings. We exploit patient migration to examine which share of regional variation in ambulatory care use in Germany can be attributed to demand factors and to supply factors, respectively. Based on administrative claim-level data we find that regional variation can be overwhelmingly explained by patient characteristics. Our results contrast with previous results for other countries, and they suggest that institutional rules in Germany successfully constrain supply-side variation in ambulatory care use between German regions. – – Die Gesundheitsversorgung weist hohe regionale Variation auf. Jedoch sind die Ursachen für regionale Variationen unzureichend erforscht und sie unterscheiden sich je nach Land und institutionellem Setting. Wie nutzen Daten zur Patientenmigration um zu untersuchen, zu welchem Anteil regionale Variationen in der ambulanten Versorgung in Deutschland über Nachfrage- versus über Angebotsfaktoren erklärt werden können. Unter Nutzung administrativer Versicherungsdaten finden wir, dass regionale Variationen zum überwiegenden Anteil durch Patientencharakteristika erklärt werden können. Unsere Ergebnisse deuten im Gegensatz zu früheren Ergebnissen für andere Länder darauf hin, dass institutionelle Regeln in Deutschland erfolgreich angebotsseitige Variation in der ambulanten Versorgung zwischen deutschen Regionen eindämmen.
Keywords: I11; I13; H51; 330; Healthcare spending; regional variation; Germany